Adolescent help-seeking: an exploration of associations with perceived cause of emotional distress - O'Neill, Alisha; Stapley, Emily; Rehman, Ishba; Humphrey, Neil (Frontiers in Public Health, 2023)
Background: Help-seeking is intrinsic to efforts to manage the onset, maintenance, or escalation of mental health difficulties during adolescence. However, our understanding of adolescent help-seeking remains somewhat nebulous. A greater comprehension of help-seeking behaviour from the perspective of adolescents is needed. It is also prudent to explore help-seeking behaviour in the context of perceived cause for emotional distress, particularly as causal beliefs have been found to influence help-seeking behaviour in adults. Objectives: The present study sought to categorise adolescents’ experiences of help-seeking, and to examine the extent to which these categories (or ‘types’) of help-seeking behaviour are associated with their perceptions of causal factors for emotional distress. Methods: The data for this study were drawn from interviews conducted as part of the (blinded for review). The sample comprised of 32 young people aged 11–12 years. Ideal-type analysis, a qualitative form of person-centred analysis, was used to construct a typology of adolescent help-seeking. Participants’ help-seeking ‘type’ was then compared with their perceived cause for emotional distress ‘type’. Findings: We developed four distinct categories of help-seeking: 1) guided by others who have taken notice; 2) sceptical with unmet needs; 3) motivated and solution focused; and 4) preference for self-regulation. Simultaneously, we identified principal associations between perceived cause of emotional distress – 1) perceived lack of control; 2) unfair treatment; 3) others: their actions and judgements as the catalyst; 4) concern for self and others; and 5) self as cause – and help-seeking approaches. ‘Perceived lack of control’ was most likely to be associated with ‘others who have taken notice’; ‘Unfair treatment’ with ‘sceptical with unmet needs’; ‘others: their actions and judgements as the catalyst’ with ‘motivated and solution focused’; ‘concern for self and others’ with ‘guided by others who have taken notice’; finally, ‘self as cause’ was most likely to be associated with ‘preference for self-regulation’. Conclusions: This study demonstrates meaningful and distinct categories of adolescent help-seeking and offers empirical evidence to support the assertion that perceived cause for emotional distress may influence the help-seeking approaches of adolescents.